Italians in cases of conflicts and tensions on coffee plantations of the judicial district of Araraquara, 1890-1914 - Teixeira, Rosane Siqueira (Cadernos CERU, 2006)
This article approaches cases of conflicts characterized for physical, moral, economic and racial the violence, for work questions, that involve deriving Italian immigrants of diverse regions of Italy and other ethnic groups, using as source criminal records. This research aims at to understand the values that guided a violent behavior in the daily conflicts, investigating the solidarity possibilities between the ethnic groups in the individual actions, mainly between the Italians. In this perspective, the work evidenced that the regional differences between the Italians limited the solidarity of the group, over all of the northern ones and of central Italy in relation to the meridionals. The analysis of the criminal records also evidenced that the main values that guided a violent behavior in the daily conflicts were to receive a wage just and to have movement freedom. These values had been verified for all the ethnic groups in question.